Evaluation of relationship between large-scale atmospheric circulation patterns with precipitation over northwestern Iran in the northern hemisphere - Asheri, Emamali (The Turkish Online Journal of Design Art and Communication, 2016)
The impact of teleconnections upon the surface climate has largely been examined via a response in monthly mean temperature or total precipitation. In this paper, for the purpose of determining relationships between teleconnection indices and precipitation, the relationship between 13 patterns of teleconnection and Monthly precipitation for 24 stations in Northwestern Iran were during the period 1992-2011, analyzed and calculated.Finally, the spatial distribution of the correlation between this indices and stations of study area was drawn and its zoning was prepared by use of Kriging method, in GIS software. the results indicate that MEI, NAO, AO and SOI are respectively significant patterns among all those and most significant relationship is related to correlation between NAO index and precipitation of jolfa station with correlation coefficients close to 0.735.
Keywords: Teleconnection; Precipitation; Correlation; Kriging; Northwestern Iran